Review of the standard and importance of oral care in residential care homes for the elderly, and factors that affect provision of care - Gerc, Susan (The University of Edinburgh, 2013)
Due to an ageing demographic, many elderly adults will depend on care either at home or in residential care homes. Currently statistics indicate approximately 450,000 people reside in care homes, with an anticipated rise to 1,130,000 by 2051 This, coupled with an improvement in oral health, has resulted in an increasing number of dentate elderly. The number of edentulous adults has fallen from 21% in 1988, to 13% in 1998, resulting in an increase in demand for geriatric dentistry in residential care homes, which research has demonstrated remains unfulfilled. Although there may be exceptions, the standard of geriatric oral care would appear to be unsatisfactory, and in some cases extremely poor. More than a third of elderly people over the age of 75 fail to receive dental attention. Medication in the elderly can cause a reduction in salivary flow which, combined with increased gingival recession, often results in root caries and mucosal infections. The need for an improvement in oral hygiene often comes at a time when manual dexterity may be failing, resulting in lower levels of oral hygiene maintenance. In some cases, a form of cognitive impairment is present, often as a result of dementia. Many residents may have full or partial dentures, and this creates the separate and additional problem of denture care. All ofthese factors often mean assistance is required with oral care, which is not always provided. There are numerous factors which contribute to this situation and these need to be fully identified and addressed. The more salient issues will be discussed further. Many studies have assessed individual factors which affect care provision. Issues which contribute to poor care include: • The level of co-operation from the residents A lack ofsuitable treatment facilities • Knowledge of care home staff/insufficient education • Attitudes of dental professionals and residential home staff • Lack of effective, readily available, and implemented guidelines Despite the large amount of research in this topic, the main issues appear to remain unresolved. The National Health Service (NHS) faces a challenge to provide good oral care for the elderly and it struggles to cope with an ageing population. In 2005, the Scottish Government introduced "An action plan for improving oral health and modernising the NHS dental service in Scotland". This plan aimed to address the issues facing Scottish dentistry. The plan considered older adults in residential care, and the Scottish government proposed that NHS boards would develop oral health support programmes with compliance monitoring. Some changes have been implemented, such as the introduction of “LifeSmile” in NHS Lothian. Similar schemes in Scotland include the Fife Care Home Award and The North Ayrshire Pilot Project. These schemes differ slightly, but have the same aim of improving oral health in the elderly population. Their impact is only now being assessed and so discussion on this topic will be limited. The lack of oral care provided to elderly residents will affect a large proportion of the population, either directly or indirectly. We should all expect an acceptable quality of life when we reach an age when we are no longer able to care for our own health. Addressing this topic is therefore paramount. This review will consider various studies which assess the importance and standard of oral care in residential homes. Also explored are the barriers to providing care, and methods by which oral health can be improved.
Keywords: nursing homes; oral care; oral care standards; care staff education; oral health; standards of care